Long-Term Deformation Analysis of Recycled Construction Waste Subgrade Filler - Zhe Li; Shihao Yan; Lulu Liu; Baosen Dai; Wenjing Dong (Advances in Civil Engineering)
The application of construction waste to subgrade has important economic and environmental significance. In order to study the long-term deformation characteristics of recycled construction waste filler, a series of laboratory tests and field measurement have been carried out. Through compaction, sieving, and California bearing ratio (CBR) tests, the gradation and CBR value of recycled construction waste filler meet the requirements of expressway subgrade. Long-term deformation tests include laboratory creep tests and field settlement measurement. The creep tests were carried out for about 500 days by a self-made consolidation creep instrument, the creep type of recycled construction waste filler under the test load is stable creep, as the load increases, not only the creep deformation increases but also the time to reach creep stability is longer, and the breakage and compaction of particles are the main reasons for long-term deformation. Through measurement and analysis, it is found that the settlement stability of the construction waste subgrade takes a long time; after the operation of road, the settlement of the subgrade has grown rapidly. Furthermore, the Burgers model can be used to predict the deformation of creep tests, and the maximum settlement of construction waste subgrade can be predicted. The research can provide reference for the application of recycled construction waste filler, and it is conducive to the promotion of construction waste subgrade.